The fungal ecology of the Brassington Formation (Middle Miocene) of Derbyshire, United Kingdom, and a new method for palaeoclimate reconstruction - Pound, Matthew J.; Nuñez Otaño, Noelia B.; Romero, Ingrid C.; Lim, Michael; Riding, James B.; O’Keefe, Jennifer M. K. (Frontiers in Ecology and Evolution, 2022)
Fossil fungi from periods warmer than modern climates provide unique insights into the future impacts of anthropogenic climate change. Here we report the fossil fungal assemblage from the late Middle Miocene Kenslow Member of central England, associated with climatic conditions even warmer than the present day. The identification of 110 morphotypes, which primarily relate to moist environments and the presence of wood, have been used to develop a new nearest living relative palaeoclimate reconstruction. The fungal assemblage indicates a Köppen-Geiger climate class, represented by temperate conditions, no dry season, and warm summers. This new fungal-based reconstruction technique holds exciting potential to explore critically important but poorly understood palaeoenvironments, and the resulting qualitative inferences align well with previously published palaeobotanical quantitative estimates of palaeoclimate. These findings show that diverse fungal assemblages can successfully be used to reconstruct past climates for the first time.